Unsur-Unsur Gramatika Arab Pada Buku Ajar Bahasa Arab Kelas XII dan Inovasi Model Pembelajarannya - Sunarko, Asep; Fahrurrozi, Fahrurrozi; Musidah, Rofidhotul; Aslamiah, Siti Syaibatul; Aisy, Rifdatul; Prayogi, Galih Yoga; Said , Umar (Al Jabiri: Jurnal Ilmiah Studi Islam, 2024)
This study was carried out with the aim of finding out several elements of Arabic grammar in Arabic textbooks and describing the problems of learning Arabic at MAN 1 Wonosobo. This research uses qualitative research in the form of field research. By using primary data sources directly through books, journals, etc., and secondary data, namely indirect sources through observations and interviews. So the data collection technique is carried out in accordance with the search for materials related to the research, then continues with specific data. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of the research show that grammatical elements are the most important part in studying linguistics, grammar in Arabic is usually called nahwu-sharaf. Nahwu talks about the interweaving or relationship of one word with other words that form a phrase or sentence, while sharaf discusses the internal aspects of words.